Global growth on life support? The contributions of fiscal and monetary policy since the global financial crisis - Ursel Baumann; David Lodge; Mirela S. Miescu (European Central Bank (ECB), 2019)
This paper compares the role of monetary and fiscal policy shocks in advanced and emerging economies. Using a model with a hierarchical structure we capture the variability of GDP response to policy shocks both between and within the groups of advanced and emerging countries. Our results provide evidence that fiscal policy effects are heterogeneous across countries, with higher multipliers in advanced economies compared to emerging markets, while monetary policy is found to have more homogeneous effects on GDP. We then quantify the policy contribution on GDP growth in the last decade by means of a structural counterfactual analysis based on conditional forecasts. We find that global GDP growth benefited from substantial policy support during the global financial crisis but policy tightening thereafter, particularly fiscal consolidation, acted as a significant drag on the subsequent global recovery. In addition we show that the role of policy has differed across countries. Specifically, in advanced economies, highly accommodative monetary policy has been counteracted by strong fiscal consolidation. By contrast, in emerging economies, monetary policy has been less accommodative since the global recession.
Keywords: C32; E42; E52; 330; fiscal policy; monetary policy; panel VAR; conditional forecast